Dynamics of COVID-19 transmission in Dhaka and Chittagong: Two business hubs of Bangladesh - Zakaria Shams Siam; Md. Arifuzzaman; Md. Salik Ahmed; Faisal Ahamed Khan; Md. Harunur Rashid; Md. Shariful Islam (Elsevier, 2021)
Background: Having inadequate health care systems and poor socio-economic infrastructure, Bangladesh has been braving to contain the impact of current COVID-19 pandemic since March, 2020. To curb the diffusion of COVID-19, the local government has responded to the outbreak by enforcing a set of restricted measures on economic and social activities across the country. Objectives: Here, we aim to assess the propagation of COVID-19 by estimating the coronavirus active cases and mortality rate in two major business hubs of Bangladesh, namely Dhaka and Chittagong city under flexible lockdown conditions. Methods: We apply a data-driven forecasting model using Susceptible, Exposed, Infected, Recovered and Deaths status through time to deal with coronavirus outbreak. Results: The epidemiological model forecasts the dire consequences for Dhaka city with 2400 death cases at the end of December, 2020, whereas Chittagong city might experience 14% more deaths than Dhaka if the severe restrictions are not implemented to control the pandemic. Conclusion: Although lockdown has a positive impact in reducing the diffusion of COVID-19, it is disastrous for human welfare and national economies. Therefore, a unidirectional decision by the policymakers might cost a very high price on either way for a lower-middle-income country, Bangladesh. In this study, we suggest a fair trade-off between public health and the economy to avoid enormous death tolls and economic havoc in Bangladesh.